2018
DOI: 10.1039/c8ta04537b
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of oxygen with halide perovskites

Abstract: Thermodynamics shows halide perovskites to be highly unstable against oxygen. Light accelerates O2 interaction kinetics. The materials stays metastable in the dark.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

17
198
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 166 publications
(225 citation statements)
references
References 43 publications
17
198
0
Order By: Relevance
“…From above simulations, it is clear that the spontaneous diffusion of oxygen in lattice of perovskite is difficult at room temperature. This is in agreement with a recent experimental work by Senocrate et al, in which the incorporation of O 2 in MAPbI 3 films has been found to be poor and sluggish. At higher temperatures (>323 K), the phase transition from the tetragonal to the cubic reduces the interspace between the inorganic frameworks, leading to more sluggish oxygen diffusion.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…From above simulations, it is clear that the spontaneous diffusion of oxygen in lattice of perovskite is difficult at room temperature. This is in agreement with a recent experimental work by Senocrate et al, in which the incorporation of O 2 in MAPbI 3 films has been found to be poor and sluggish. At higher temperatures (>323 K), the phase transition from the tetragonal to the cubic reduces the interspace between the inorganic frameworks, leading to more sluggish oxygen diffusion.…”
Section: Resultssupporting
confidence: 93%
“…Specifically, the influence of oxygen and light on MAPbI 3 has attracted great attention recently, and the study on improving the stability of MAPbI 3 against photo‐oxidation is springing up . Zhang and Sit have reported a pathway for breaking of the local octahedral Pb–I structure and the formation of the PbO precursor .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…They found that photogenerated electrons in a device can reduce oxygen and form superoxide O 2 − , which can effectively bind to electron traps. However, superoxide O 2 − species are not always advantageous to perovskites and have been shown to be the origin of the degradation of perovskite films under light and oxygen exposure . We therefore minimized light exposure to our samples during processing, storage, and measurement.…”
Section: Resultsmentioning
confidence: 99%